CT Evaluation of Coronary Artery Disease - Pavone, Paolo. (Springer Milan, 2009)
Cardiovascular diseases are the leading cause of death in Western countries. In non-fatal cases, they are associated with a decreased quality of life as well as a substantial economic burden to society. Most sudden cardiac events are related to the complications of a non-stenosing marginal plaque. For this reason, the ability to properly identify the atherosclerotic plaque with a rapid, non-invasive technique is of utmost clinical interest in therapeutic planning. Coronary CT angiography produces high-quality images of the coronary arteries, in addition to defining their location and the extent of the atherosclerotic involvement. Proper knowledge of the equipment, adequate preparation of the patient, and accurate evaluation of the images are essential to obtaining a consistent clinical diagnosis in every case. With its clear and concise presentation of CT imaging of the coronary arteries, this volume provides general practitioners and cardiologists with a basic understanding of the technique. For radiologists with no direct experience in cardiac imaging, the book serves as an important source of information on coronary pathophysiology and anatomy.